2011
DOI: 10.1111/j.1467-8659.2011.01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Component‐wise Controllers for Structure‐Preserving Shape Manipulation

Abstract: Recent shape editing techniques, especially for man-made models, have gradually shifted focus from maintaining local, low-level geometric features to preserving structural, high-level characteristics like symmetry and parallelism. Such new editing goals typically require a pre-processing shape analysis step to enable subsequent shape editing. Observing that most editing of shapes involves manipulating their constituent components, we introduce component-wise controllers that are adapted to the component charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
109
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(110 citation statements)
references
References 32 publications
1
109
0
Order By: Relevance
“…Our work also shares resemblance to the large body of methods on structure-based shape analysis and modeling [17], [18], [19], [20], [21], [22], [23], wherein high-level shape structures are identified with low-dimensional parts of different sizes, positions, and interactions. Gal et al [17] demonstrated that working with a set of 1D feature curves extracted from engineered objects, and preserving their intra-and inter-relations while deforming the shapes lead to an intuitive manipulation framework.…”
Section: Related Workmentioning
confidence: 67%
“…Our work also shares resemblance to the large body of methods on structure-based shape analysis and modeling [17], [18], [19], [20], [21], [22], [23], wherein high-level shape structures are identified with low-dimensional parts of different sizes, positions, and interactions. Gal et al [17] demonstrated that working with a set of 1D feature curves extracted from engineered objects, and preserving their intra-and inter-relations while deforming the shapes lead to an intuitive manipulation framework.…”
Section: Related Workmentioning
confidence: 67%
“…Shape deformation is a longstanding topic in geometry processing [20]. The shape deformation methods mainly fall into two classes: those that aim to preserve the shape's local properties, such as curvature, differential coordinates [21], [22], [23], and those that aim to preserve global structures, such as symmetry and inter-part relations [24], [25], [26]. Li et al [27] deform input man-made objects to make them amenable to stacking.…”
Section: Related Workmentioning
confidence: 99%
“…Each node in the graph corresponds to a component, while each edge denotes a contact or symmetry relation (see Figure 4). We fit each component with a primitive (in our system cuboid and cylinder, computed via PCA); we call such a primitive a proxy, which is later used to guide the deformation of the underlying component [26]. We compute the contact information between adjacent components by considering their point-to-point distances.…”
Section: Shape Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, understanding the higher-level representations of 3D models has received considerable interest (see survey [11]), including symmetry detection [12,13,14], upright orientation inference [15] and shape abstractions [16]. Benefitting from these techniques, a wide spectrum of applications are spawned, such as shape manipulation [17,18,19], shape synthesis [20], motion analysis [21,22,23,24] and computational furniture design [25]. In addition, many works focus on the analysis of individual parts within an input model, which are similar to our framework.…”
Section: Related Workmentioning
confidence: 99%